2007
DOI: 10.2478/s11756-007-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved Agrobacterium-mediated genetic transformation of GNA transgenic sugarcane

Abstract: Six plasmids carrying a snowdrop lectin (Galanthus nivalis agglutinin, GNA) and one of three selection markers were successfully transferred into two sugarcane cultivars (FN81-745 and Badila) via Agrobacterium-mediated transformation. Agrobacterium strains LBA4404, EHA105 and A281 that harboured a super-binary vector were used for sugarcane transformation. The use of the hygromycin (Hyg) resistance gene (hpt II), phosphinothrincin (PPT) resistance gene (bar) or G418 resistance gene (npt II) as a screenable mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 24 publications
2
25
0
2
Order By: Relevance
“…To date, sugarcane has been transformed by either Agrobacterium tumefaciens or Biolistics methods (Manickavasagam et al 2004;Zhangsun et al 2007;Altpeter and Oraby 2010;Joyce et al 2010;Khamrit et al 2012). The transformed plants were regenerated using direct, indirect organogenesis or somatic embryogenesis (Arencibia et al 1998;Manickavasagam et al 2004;Attia et al 2005;Lakshmanan et al 2006;Eldessoky et al 2011;Taparia et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To date, sugarcane has been transformed by either Agrobacterium tumefaciens or Biolistics methods (Manickavasagam et al 2004;Zhangsun et al 2007;Altpeter and Oraby 2010;Joyce et al 2010;Khamrit et al 2012). The transformed plants were regenerated using direct, indirect organogenesis or somatic embryogenesis (Arencibia et al 1998;Manickavasagam et al 2004;Attia et al 2005;Lakshmanan et al 2006;Eldessoky et al 2011;Taparia et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the markers used in selecting for transformed plants include the hygromycin phosphotransferase gene ( hph ) or the bialaphos resistance bar gene (Table 11.1 ). However, more recently, the neomycin phosphotransferase II ( npt II) gene has been successfully shown to be ef fi cient in selecting transformed sugarcane callus (Zhangsun et al 2007 ) . Transformed shoots of the commercial variety Q117 were only regenerated when calli were inoculated with an Agrobacterium strain harboring a plasmid with the npt II gene as opposed to the one with the hph gene, suggesting that the selection system is important for producing transgenic shoots (Joyce et al 2010 ) .…”
Section: Agrobacterium -Mediated Transformationmentioning
confidence: 99%
“…High GC content in all three of these transgenes, i.e. up to 68.0% in bar gene (Zhang et al 2007), 56.7% in aprotinin (Shantaram 1999) and 48.5% in cry1Ab (Arvinth et al 2010) could be the reason for their stable expression after repeated vegetative propagation. The role of high GC content and codon usage in sugarcane transgene expression was clearly demonstrated by Weng et al (2006Weng et al ( , 2010 who reported a progressive increase in the Cry1Ac content and corresponding insect resistance by increasing the GC content from the native 37.4% to 47.5% and 54.8%.…”
Section: Transgene Expressionmentioning
confidence: 98%
“…The four factors of: (1) strength of the promoters that drive the candidate gene, (2) gene silencing, (3) GC content and codon usage, and (4) somaclonal variation largely influence the success of transgenic lines (Zhang et al 2007). The rice polyubiquitin (RUBIQ2) promoter seems to be the strongest for sugarcane (Zhang et al 2007), but the maize ubi-1 promoter has been most commonly used for insect resistant genes in sugarcane (Table 1). Although the maize ubi-1 promoter is constitutive, it does not express the transgene to the same level in all plant organs, e.g.…”
Section: Transgene Expressionmentioning
confidence: 99%